Value of p53 and estrogen receptors immunohistochemical staining in endometrial carcinoma - Opric, Dejan; Suskic, Amer; Suskic, Sanela Halilovic; Nikolic, Gorana; Filipovic, Isidora (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Since there are many articles dealing with estimating prognostic and diagnostic value of ER and p53, using different, usually complex ICH interpretation methods, we wanted to evaluate significance of p53 and ER ICH positivity in endometrial carcinoma, using easily applicable criteria that would help pathologists and clinicians to be sure in ICH findings noted in the report. Methods: This paper deals with data of the patients treated for endometrial carcinoma in Public Hospitals in Travnik, gynecological department in the period from 1st January 2013 to 1st January 2019. The study included 97 women with endometrial carcinoma, with ages ranging from 42 to 90 years (mean of 64 years). Sample consisted of 72 cases (74.2%) of endometrioid and 25 cases (25.8%) of non-endometrioid carcinoma. Results: p53 expression was observed in 13.8% carcinomas of the endometrioid type and in 68% carcinomas of non-endometrioid type, while estrogen receptors were more frequently observed in tumors of the endometrioid type (61%) in contrast to non-endometrioid type (28%). Among 72 cases, those with grade I expressed estrogen receptors (26 out of 34 cases - 72%) more frequently than those with grades II and III. Frequency of p53 positivity was significantly higher at higher grades (grade I - 5.8%, grade II - 11.5%, grade III - 71.4%). Stage I carcinomas showed p53 staining less frequently (22.2%) that carcinomas diagnosed at later stages (31.5%). Conclusions: Using 80% nuclei stained as threshold for p53 positivity, we concluded that p53 is marker of high-grade endometrial carcinomas: high grade endometrioid and non-endometrioid carcinomas. Using 1% of cells as threshold for ER positivity, we confirmed that ER are common in endometrioid type carcinoma, in contrast to non-endometrioid type. Although observed, higher frequency of ER in tumors with lower grade and stage was not statistically confirmed in our study population.